El exilio europeo del nacionalismo gallego a partir de 1939. Francia y la figura de Xohán Xosé Plá - Uxío-Breogán Diéguez Cequiel (Cahiers de Civilisation Espagnole Contemporaine, 2017)
The presence of the Galician Republicans in Europe, following the flight of the Democrats who avoided falling into the hands of the putschists from July 1936, was accentuated in the spring of 1939 after the victory of the fascists commanded by Francisco Franco. Even though the presence of Galician sovereignists was weak compared to the whole of Galician exile, whose main nucleus was in South America, it is true that it has a great qualitative interest if we consider its activity. The final victory of the army raised against the republican legality provoked the reception of the Democrats on the European continent; Democrats who would have had the same fate as thousands of republicans and republicans who had been murdered or, at best, imprisoned if they had not been able to flee the Spanish state. Among these exiles, there were frames of Galician sovereignty who had an influence in various sectors of exile, not exclusively Galician nationalism. It is in this context that the figure, very little studied, emerges of the galicianist established in the South of France, Xohán Xosé Plá Fernández (1906-?).